1988
DOI: 10.1007/bf01092865
|View full text |Cite
|
Sign up to set email alerts
|

High temperature storage of potato (Solanum tuberosum L.) for processing ? a feasibility study

Abstract: Tubers of three potato cultivars were stored at room temperature (20-39 degrees C, 30-75% RH), under an insulated storage run on passive evaporative cooling (16-30 degrees C, 70-90% RH) and a refrigerated storage (2-4 degrees C, 90-95% RH) for 14 weeks and studied periodically for storage losses, reducing sugar content and dry matter percent of tubers, in order to explore the possibility of storing potatoes for processing at higher temperatures. Physiological losses in tubers remained less than 10% until 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is worth mentioning that changes in the content of various nutrients in potatoes are a commonly known phenomenon. For example, a decrease in concentration of reducing sugar [29], starch [30] and vitamin C [31, 32] in potatoes during storage has been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that changes in the content of various nutrients in potatoes are a commonly known phenomenon. For example, a decrease in concentration of reducing sugar [29], starch [30] and vitamin C [31, 32] in potatoes during storage has been described.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the concentration of some nutrients in potatoes decreases during a long-term storage [2932]. Therefore, it was investigated whether storage time influences the concentration of KYNA.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (1999) found the similar result in low temperature storage condition. RS content of potatoes was remarkably low in tubers stored at the room temperature and under evaporative cooled storage as compared to the tubers stored in refrigerated storage (Mehta and Kaul, 1988).…”
Section: Reducing Sugar Contentmentioning
confidence: 81%
“…According to Burton (1966) and Schippers (1971), weight loss is caused by transpiration and sprouting. Mehta & Kaul (1988) report a 9-10% weight loss after 60 days of storage at 2-4 o C and a RH of 90-95% for three different, not nematode infected, cultivars. That is only slightly lower than the 12% weight loss after 60 days at 4 o C in this experiment.…”
Section: Weight Loss and Sprouting: Experimentsmentioning
confidence: 99%